2018
DOI: 10.6004/jnccn.2017.7028
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Quality Beyond Average Muscle Attenuation: A Proposal of Skeletal Muscle Phenotypes to Predict Short-Term Survival in Patients With Endometrial Cancer

Abstract: Increasing evidence links sarcopenia and cancer prognosis, but limited data have focused on whether and to what extent muscle radiodensity can impact cancer outcomes. This study was conducted to investigate whether skeletal muscle mass, when divided into subranges of low or high radiodensity, improves prediction of short-term survival in patients with endometrial cancer (EC). Four skeletal muscle phenotypes were proposed to assess which is the best predictor of 1-year mortality. Patients with EC who had CT ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 3 publications
0
25
0
1
Order By: Relevance
“…CT images can provide objective body composition measures and are widely used in staging, radiotherapy planning, and follow‐up in patients with advanced EC. Rodrigues and Chaves reported that pretreatment sarcopenia and myosteatosis were predictors of poor short‐term survival . We measured pretreatment and post‐treatment body compositions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CT images can provide objective body composition measures and are widely used in staging, radiotherapy planning, and follow‐up in patients with advanced EC. Rodrigues and Chaves reported that pretreatment sarcopenia and myosteatosis were predictors of poor short‐term survival . We measured pretreatment and post‐treatment body compositions.…”
Section: Discussionmentioning
confidence: 99%
“…61 The body composition measurement using clinically available CT images could be imaging biomarkers of survival outcomes in advanced stage EC. 38,39,47 CT images can provide objective body composition measures and are widely used in staging, radiotherapy planning, and follow-up in patients with advanced EC. Rodrigues and Chaves reported that pretreatment sarcopenia and myosteatosis were predictors of poor short-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations